2014
DOI: 10.17306/j.afs.2014.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Infl uence of the marinating type on the morphological and sensory properties of horse meat

Abstract: Marinating is a process in which meat is treated with different solutions for the purpose to enhance its appearance, to improve the quality, and to extend its shelf-life [Latif 2001]. On the other hand, marinade solutions enhance juiciness and tenderness of meat, and by increasing the quantity of added water they increase the yield of the fi nished product [Sheard and Tali 2004].Depending on the type of ingredients used, marinade solutions are: alkaline (containing salt-phosphate mixtures), acid (containing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
(12 reference statements)
2
13
1
Order By: Relevance
“…The observed AV was not surprising because these samples had oil addition and as a result the lipolytic processes in wateroil marinated sheep were found higher. The results for AV were in accordance with our other studies about water-oil marinating of horse meat evaluated by tested committee with lower scores due to negative rancid odor and taste [36].…”
Section: Acid Value (Av)supporting
confidence: 91%
See 1 more Smart Citation
“…The observed AV was not surprising because these samples had oil addition and as a result the lipolytic processes in wateroil marinated sheep were found higher. The results for AV were in accordance with our other studies about water-oil marinating of horse meat evaluated by tested committee with lower scores due to negative rancid odor and taste [36].…”
Section: Acid Value (Av)supporting
confidence: 91%
“…Oppositely, the results obtained for lactate marinated meat (AC48) are difficult to explain. On the one hand many researches prove the antioxidant effect of sodium lactate [9][10][11]36]. On the other hand the data for POV and TBARS determination showed that lipid oxidation significantly increases after marinating with 2% sodium lactate.…”
Section: Tbarsmentioning
confidence: 99%
“…On the other hand, acid solutions with organic acids or their salts have been used for the same purpose [25]. In addition, Vlahova-Vangelova et al [26] reported that alkaline marinated solutions had a stronger effect on horsemeat than acid solutions, resulting in a lower internal pH and a softening of the tissue.…”
Section: Ph Determinationmentioning
confidence: 99%
“…Vlahova-Vangelova et al [64] conducted a study to demonstrate the effect of the type of marinating on the morphological and sensory properties of horsemeat. The authors of the study for marinating horsemeat used alkaline marinate (AL) consisting of 2% polyphosphates and 2% sodium chloride brine; acid marinate (AC) consisting of 2% sodium lactate and 2% sodium chloride brine; water-oil emulsion (50/50) containing 2% sodium chloride (WO); and marinate containing 2% sodium chloride (SC).…”
Section: The Use Of Solutions Of Selected Substances In the Marinating Processmentioning
confidence: 99%